PSYCHOLOGICAL CONTENT OF DEVELOPING SCIENTIFIC RESEARCH COMPETENCES OF MASTER'S STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article discusses the pedagogical and psychological content of developing scientific research competencies of master's students . It also shows that master's students should be aware of the content of scientific approaches, concepts, theories, and the latest information in their discipline during their studies at a higher educational institution and their subsequent professional development.